Pemanfaatan Konsep Pentahelix dan Pengoptimalan Sistem Drainase sebagai Upaya Penanganan Banjir di Situs Keraton Kaibon - Surya, Pratama Dharma; Nabila, Kharisma; Nisa, Resty Khairul; Zein, Yasmin Shafitri (JANUS, 2023)
The Kaibon Palace Cultural Heritage Site is one of the palaces built during the Kesultanan Banten era. It was constructed in 1815 AD. In 1832 AD, the palacewas destroyed by the Dutch East Indies government However, the remains of the palace buildings still exist. These relics have significant value as witnesses of cultural development and the history of Islam in Banten. The purpose of this study is to identify the causes of flooding at the Kaibon Palace and find solutions to these problems. The research method is conducted online through literature study, virtual observation, and qualitative data analysis. The results show that the flooding problem is caused by the process of shallowing of canals and rivers. This occurs, among other things, a lack of concern for the situation of the various stakeholders. this study recommends that the flood problems in the Kaibon Palace can be overcome by utilizing the pentahelix concept and optimizing the drainage system. Utilization of the pentahelix concept is carried out through an active role of the government, academics, business people, community, and media. Optimization of the drainage system is carried out by revitalising the old drainage system and building a new proper drainage system. These recommendations have the potential to be implemented as a consideration in maintaining and preserving the Kaibon Palace in order to create a site area and surrounding environment that is free from the threat of flood disasters and is beneficial for the community. === Situs Cagar Budaya Keraton Kaibon merupakan salah satu keraton peninggalan masa Kesultanan Banten yang dibangun pada tahun 1815 M. Kompleks bangunan ini dihancurkan oleh Pemerintah Hindia Belanda pada tahun 1832 M. Meskipun demikian, masih ditemukan sisa-sisa bangunan keraton yang memiliki nilai penting sebagai bukti perkembangan kebudayaan dan pengaruh Islam di Banten. Penelitian ini bertujuan untuk mengidentifikasi penyebab banjir pada Keraton Kaibon dan mencari solusi untuk mengatasi permasalahan tersebut. Pengeumpulan data dilakukan secara daring melalui studi literatur dan observasi virtual, selanjutnya data dianalisis secara kualitatif. Hasil penelitian ini menunjukkan masalah banjir lebih disebabkan oleh proses pendangkalan kanal dan sungai. Keadaan ini diakibatkan antara lain sikap kurang peduli dari berbagai pihak pengampu kepentingan. Hasil analisis data merekomendasikan penanganan permasalahan banjir di Keraton Kaibon dapat diatasi dengan pemanfaatan konsep pentahelix dalam pengoptimalan sistem drainase. Pemanfaatan konsep pentahelix dilakukan melalui peran aktif antara pihak pemerintah, akademisi, pelaku bisnis, komunitas, dan media. Pengoptimalan sistem drainase dilakukan dengan memperbarui dan membangun sistem drainase yang layak guna. Rekomendasi tersebut berpotensi diterapkan sebagai pertimbangan dalam menjaga dan melestarikan Keraton Kaibon guna menciptakan kawasan situs dan lingkungan sekitarnya yang bebas dari ancaman bencana banjir dan bermanfaat bagi masyarakat.